PENENTUAN KONSENTRASI KEMATIAN KALUS TEBU (Saccharum officinarum) VARIETAS BL DAN PS-862 PADA SELEKSI In Vitro UNTUK KETAHANAN TERHADAP SALINITAS - - Parnidi; Nurlaila Shofianita; Tutik Nurhidayati (Agric, 2016)
ABSTRACTSalinity (salt stress) is one of the different causes of decline in crop yields and productivity of sugarcane. One strategy for optimizing the production of sugarcane on saline land required tolerant varieties of salinity. This research was conducted to determine NaCl concentration that caused more than > 90% callus death on sugarcane (S officinarum) tissue culture and to investigate the protein profile of sugarcane callus BL and PS-862 varieties on saline (NaCl) stress condition. Sugarcane BL and PS-862 varieties were obtained from tissue culture. and those callus were sub-cultured in salinity media with composition of MS (Murashige-Skoog) as base medium and NaCl in various concentration (0%; 0.25%; 0.5%; 0.75%; and 1%). The results showed condition of NaCl addition on media by 1% concentration cause alteration on morphology of callus that 75% part of whole tissues become dark brown coloured that indicating the tissues death. At four weeks after sub-culture, the calli on both varieties obtain score 4. Lethal percentage of both varieties BL and PS-862 in 1% NaCl was 91,67%. This result were supported by protein profile analysis. that a thinner protein band in 1% NaCl treatment compared with control. This is indicating that in salinity stress causing the decrement of protein expression.